2002
DOI: 10.1073/pnas.102168499
|View full text |Cite
|
Sign up to set email alerts
|

Identification of β-cell-specific insulin gene transcription factor RIPE3b1 as mammalian MafA

Abstract: Of the three critical enhancer elements that mediate ␤-cell-specific and glucose-responsive expression of the insulin gene, only the identity of the transcription factor binding to the RIPE3b element (RIPE3b1) has remained elusive. Using a biochemical purification approach, we have identified the RIPE3b1 factor as a mammalian homologue of avian MafA/L-Maf (mMafA). The avian MafA is a cell-type determination factor that expressed ectopically can trigger lens differentiation program, but no mammalian homologue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
235
1
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(250 citation statements)
references
References 41 publications
10
235
1
4
Order By: Relevance
“…Previous studies have identified a b-cell-restricted RIPE3b-binding factor, called the RIPE3b1 activator, that appears in response to glucose in pancreatic b-cell nuclear extracts [38]. Very recently, two papers have been published stating that the RIPE3b1 activator is MafA [29,30]. Our data confirmed their observations and added new information about RIPE3b recognition by large Maf transcription factors.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have identified a b-cell-restricted RIPE3b-binding factor, called the RIPE3b1 activator, that appears in response to glucose in pancreatic b-cell nuclear extracts [38]. Very recently, two papers have been published stating that the RIPE3b1 activator is MafA [29,30]. Our data confirmed their observations and added new information about RIPE3b recognition by large Maf transcription factors.…”
Section: Discussionsupporting
confidence: 85%
“…Our investigation of zebrafish large Mafs indicated that SMafs might play important roles in somitogenesis. Very recently, it has been reported that human and mouse MafA are expressed in the pancreatic b cells of the islet of Langerhans and are the potential regulators of insulin gene expression [29,30]. To elucidate the detailed function of MafA/L-Maf/SMaf1 in mammals, we isolated mouse MafA, the homologue of zebrafish SMaf1, and analyzed its expression profile.…”
mentioning
confidence: 99%
“…3a). Mafa is an important transcription factor for insulin gene expression [27]. Similarly, Ins1, Ins2, Egfp, Pdx1, Mrfp, Mafa, Nkx6-1 and Glut2 were also downregulated by activin A treatment in MIN6 cells (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…The overexpression of Beta2 in the hamster insulinoma cell line In1024 enhanced human insulin gene transcription [10], whereas mice deficient in BETA2 showed a reduction of insulin-producing beta cells and failed to develop mature islets [15]. MafA was identified as a glucose-regulated transcription factor binding to the rat insulin promoter element 3b (RIPE3b) within the insulin gene promoter [16,17], containing the C1 and A2 elements [18]. This transcription factor appears to be responsible for the betacell-specific expression of insulin [19].…”
Section: Introductionmentioning
confidence: 99%